Global health policy: Does the 90-90-90 treatment target address the burden of HIV/AIDS? - Asfaw, Bisrat; ADAMU, VE (Orapuh Journal, 2020)
Acquired Immune Deficiency Syndrome (AIDS) is caused by the virus known as the Human Immunodeficiency Virus (HIV) and continues to be one of the world's most pressing public health challenges. This paper reviews the global health policy in the HIV/AIDS response, its challenges, and its impacts on addressing the burden of HIV. There is a global commitment to stopping new HIV infections, ensuring that everyone with HIV can access HIV treatment, and end the pandemic. UNAIDS's 90-90-90 goals were set to end the HIV pandemic crisis by 2020. The Goal was 90% of all people with HIV will know their HIV status, 90% of all people who know their status will be on ART, and 90% of all people receiving ART will have viral load suppression. From the UNAIDS 2018 reports, there is promising progress towards meeting the 90-90-90 target. For instance, as of 2018, 79% knew their HIV status, 78% of all people who knew their status were accessing ART, and 86% of all people receiving ART had viral suppression. Also, new HIV infections fell by 39% between 2000 and 2019. HIV-related deaths fell by 51% over the same period, and 15 million lives were saved because of appropriate policy implementation. Conversely, the new figures from the World Health Organization (WHO) and the Joint United Nations Programme on HIV/AIDS (UNAIDS) revealed progress towards ending AIDS as a public health threat by 2030 was already off track before the COVID-19 pandemic.